Potensi Bakteri Filoplan Asal Tanaman Sagu Aksesi Makanaru (Metroxylon longispinum) Sebagai Agens Hayati Terhadap Pertumbuhan Rhizoctonia solani Kuhn - Nurlette, Jahra; Leiwakabessy, Christoffol; Talahaturuson, Abraham; Uruilal, Costanza; Ririhena, Rhony Einstein; Rumahlewang, Wihelmina; Patty, Jacob Richard (Fakultas Pertanian, Universitas Pattimura, 2024)
The sago plant is a staple food for the people of Maluku and Papua and has many benefits and advantages to continue to be developed. A group of phylloplane microbes grow and spread on the surface of the leaves. The objective study is to find isolates of phylloplane bacteria from sago accession Makanaru and determine the inhibition of these bacteria against the growth of Rhizoctonia solani Kuhn. Sampling of sago plants (upper, middle, and lower leaves) was conducted in Negeri Seith, Leihitu District, Central Maluku Regency. Based on the isolation results, 21 isolates of phylloplanes bacteria were obtained and ready for further testing. From the results of hypersensitive test selection, 14 non-pathogenic isolates of phylloplane bacteria were obtained. Furthermore, tested the inhibitory power of phylloplane bacteria in suppressing the growth of the fungus, 3 phylloplane bacteria isolates were obtained with strong inhibitory, namely DA3.3, DT3.2, DT3.1 followed by 3 isolates DB4, DB4.2, and DB4.4 (medium inhibitory) which have the potential to be developed as biological agents.